Karakteristik profil pasien urtikaria akut di poliklinik kulit dan kelamin Rumah Sakit Umum Pusat (RSUP) Sanglah periode Oktober 2017- 2018 - Gede Mahadika Pradipta Atmaja; Nyoman Suryawati; Luh Made Mas Rusyati (DiscoverSys Inc., 2019)
Background: Acute urticaria is a skin disorder that is often encountered that can cause redness to respiratory obstruction so that emergency emergencies and urticaria lesions that last more than 72 hours are indicative of hospitalized patients. This study aims to describe the characteristics of acute urticaria at Dermato-Venerology Polyclinic, Sanglah General Hospital during October 2017-2018 period.Methods: A cross-sectional study was conducted using secondary data from medical records of patients with urticaria in Sanglah General Hospital in the October 2017-2018 period. Data retrieval was taken by the Total Sampling method. Distribution of research variables namely, gender, age, genetic, causative factors, were collected. Data analysis is described in the form of tables and narratives using SPSS version 20 for Windows.Results: The results showed that there were 23 acute urticaria patients in this study, the age of the most research samples was in the Adult age category with a large percentage of 60.87%, the most gender-based study sample was female gender with a percentage of 78.3%, research genetic samples most of them are in the absence of genetics, with a percentage of 91.3%, the work of most research samples in housewives with a percentage of 34.8%, the most common cause of acute urticaria is in food allergies with a percentage of 56.5%.Conclusion: The incidence of acute urticaria is most common in adulthood, female sex, housewives, and food allergies.